MENINGKATKAN KECERDASAN EMOSIONAL MELALUI METODE BERMAIN PERAN ANAK USIA 3-4 TAHUN DI KB KASIH IBU PISANG BEREBUS KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Lesmaneti '; Wilson '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: based on the results of field observations on the level of emotional intelligence of the students is still low and teachers are still teaching methods that dominate and not varied. So that needs to be given in the form of a method of learning to play a role. This study aims to determine how high the increase emotional intelligence of children after using the method of playing the role of children aged 3-4 years in KB Kasih Ibu Pisang Berebus. The research method is a method of classroom action research conducted in two cycles, each cycle consisting of several stages, namely planning, action, observation and reflection. The number of subjects in this study 15 children in KB Kasih Ibu Pisang Berebus. Data taken from the evaluation at the end of each cycle. This study involved one colleague as an observer. Based on the data obtained from the results of the percentage increase in the first cycle is 40,9% and increased in the second cycle is 60,6%. It can be thus it can be concluded that the method of playing the role can improve emotional intelligence in children 3-4 years in KB Kasih Ibu pisang Berebus District of Gunung Toar Regency Kuantan Singingi.